Expression profile of Bcl‐2 family proteins in newly diagnosed multiple myeloma patients - Cristina De Ramón; Elizabeta A. Rojas; Irena Misiewicz‐Krzeminska; Ignacio J. Cardona‐Benavides; Myriam Cuadrado; Isabel Isidro; María‐José Calasanz; Manuela Fernandez; Ramón García‐Sanz; Noemi Puig; M. Teresa Cedena; Bruno Paiva; et al. (HemaSphere)
Abstract Antiapoptotic Bcl‐2 family proteins are involved in myeloma cell survival. To date, their expression in multiple myeloma (MM) patients has mostly been analyzed at the RNA level. In the present study, we quantified for the first time the protein expression of the Bcl2‐family members using a capillary electrophoresis immunoassay in 120 newly diagnosed MM patients, aged ≤65 years, treated in the context of the PETHEMA/GEM2012 study. We found that the pattern of expression of Bcl‐2 family proteins was highly heterogeneous among patients. Although cases with t(11;14) had significantly higher levels of Bcl‐2/Bcl‐xL and Bcl‐2+Bim+Bax/Bcl‐xL ratios than those without t(11;14), the presence of this translocation was not synonymous with such high levels of expression. Conversely, some patients with other genetic alterations also showed higher levels of those ratios. Survival analysis revealed that the high expression of Bad and Puma proteins was associated with significantly longer overall survival (p = 0.001 and p < 0.001, respectively). Bcl‐2 protein ratios predicting sensitivity to venetoclax in vitro were also able to distinguish patients with shorter time to progression after triplet‐based induction therapy and ASCT. This is the first study to assess the expression of the most important Bcl‐2 family proteins by a quantitative method in a large set of MM patients according to their cytogenetic abnormalities. We shed light on the impact of these proteins on MM prognosis, which could help to consider the levels of proteins involved in apoptosis in the development of new therapeutic strategies.